Neural Substrates of Attentive Listening Assessed with a Novel Auditory Stroop Task - Christensen, Thomas A.; Lockwood, Julie L.; Almryde, Kyle R.; Plante, Elena (Frontiers in Human Neuroscience, 2011)
A common explanation for the interference effect in the classic visual Stroop test is that reading a word (the more automatic semantic response) must be suppressed in favor of naming the text color (the slower sensory response). Neuroimaging studies also consistently report anterior cingulate/medial frontal, lateral prefrontal, and anterior insular structures as key components of a network for Stroop-conflict processing. It remains unclear, however, whether automatic processing of semantic information can explain the interference effect in other variants of the Stroop test. It also is not known if these frontal regions serve a specific role in visual Stroop conflict, or instead play a more universal role as components of a more generalized, supramodal executive-control network for conflict processing. To address these questions, we developed a novel auditory Stroop test in which the relative dominance of semantic and sensory feature processing is reversed. Listeners were asked to focus either on voice gender (a more automatic sensory discrimination task) or on the gender meaning of the word (a less automatic semantic task) while ignoring the conflicting stimulus feature. An auditory Stroop effect was observed when voice features replaced semantic content as the "to-be-ignored" component of the incongruent stimulus. Also, in sharp contrast to previous Stroop studies, neural responses to incongruent stimuli studied with functional magnetic resonance imaging revealed greater recruitment of conflict loci when selective attention was focused on gender meaning (semantic task) over voice gender (sensory task). Furthermore, in contrast to earlier Stroop studies that implicated dorsomedial cortex in visual conflict processing, interference-related activation in both of our auditory tasks was localized ventrally in medial frontal areas, suggesting a dorsal-to-ventral separation of function in medial frontal cortex that is sensitive to stimulus context.